A study of herbage and seed production of lucerne (Medicago sativa L.) under different plant spacing and cutting treatments : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science at Massey University - Kowithayakorn, Lumyai (Massey University, 1978)
The present study on lucerne cv. "Wairau" was carried out in two separate trials, - a herbage and seed production trial and a seed development trial. The purpose of the first part was to investigate the effect of cutting and spacing on herbage production and subsequently on seed yield. In the second part, changes in seed weight, moisture content, and viability during various stages of seed development were studied. Results from the herbage study suggested that fresh and dry herbage yield were both affected more by plant spacing than by the height of cutting and the stage of plant development at the time of cutting. Close plant spacings resulted in higher yields of both dry matter per unit area and dry matter percentage than wide spacings. The study showed that lucerne plants in first year crops should be grown at a plant density higher than 44 plants per sq. metre and up to 100 plants per sq. metre to reach maximal herbage yield per unit area. Early cutting and high cutting gave a significantly lower herbage yield than when plants were cut late and cut at a low stubble height. Cutting and spacing treatments had a profound influence on seed yield per unit area. Seed production in lucerne, unlike herbage production, depended mainly on seed yield per plant rather than on the number of plants per unit area. Both cutting and spacing treatments affected seed yield per plant by altering the number of reproductive shoots, number of flowers per plant and the percentage of seed set. Plants grown at wide spacings produced more branches and flowers per plant and also exhibited a higher percentage seed set, thereby producing high numbers of seeds per plant. To obtain high seed yield in this variety of lucerne, plants should be grown at a plant density of approximately 11-25 plants per sq. metre. Cutting lucerne plants prior to allowing them to seed resulted in a weakening of the plants, severely depressed reproductive potential, delayed flowering time and subsequently affected flower production and percentage seed set. Lucerne plants should therefore not be cut at all in the year of plant establishment if high seed yields are expected. Seed development followed three distinct phases. The growth stage involved the period up to 22 days after pollination. At the end of the stage, 3% of seeds were germinable. The food reserve accumulation stage occupied the period from 23-40 days after pollination. Maximum seed dry weight was attained after 40 days at a seed moisture content of 58%. The ripening stage occupied the period from 41-75 days after pollination. At the end of this stage seed moisture content was approximately 14% and subsequently 6% of hard seed were found when seeds were tested immediately after harvest. Storage results in this trial indicated that immature seed tended to lose germination capacity more rapidly than mature seed. To ensure high seed quality in lucerne it was essential that seed be harvested after maturity.
Keywords: Alfalfa; Alfalfa Growth; Alfalfa Seeds